Pengaruh Desain Produk, Fitur Produk, dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone Samsung di Kalangan Generasi Z: Studi Kasus Jabodetabek - Djacinta Sephia Putri; Teti Haryati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This This study aims to determine the influence of product design, product features, and product quality on Samsung smartphone purchase decisions among Generation Z. The research uses a causal quantitative approach with the SEM-PLS analysis technique. Sampling is conducted using purposive sampling, with data collected through an online questionnaire distributed via Google Form to 130 Samsung product users. The results show that product design, product features, and product quality significantly influence purchasing decisions. The research results show that product design, product features, and product quality have a positive and significant influence on purchase decisions. Therefore, companies need to continuously improve product design, features, and quality to maintain competitiveness and attract Generation Z's interest in purchasing Samsung smartphones.